Orthopedic Trauma During Pregnancy; a Narrative Review - Meisam Jafari Kafiabadi; Amir Sabaghzadeh; Seyyed Saeed Khabiri; Mehrdad Sadighi; Amir Mehrvar; Farsad Biglari; Adel Ebrahimpour (Archives of Academic Emergency Medicine, 2022)
Introduction: Blunt traumas, like road accidents and falls, are common causes of injuries to pregnant women, and the major risk factors are young age and low socioeconomic level. Due to physiological and anatomical changes specific to pregnancy, such as changes in blood pressure and hemoglobin drop, trauma management involves certain complexities. Physical trauma is estimated to cause at least 1 complication in every 12 pregnancies. This study aims to evaluate orthopedic trauma during pregnancy and appreciate the different approaches to circumvent the resultant challenges.